The Role of Audit Committees in Activating the Governance of Banks: An Exploratory Study from the Point of View of Auditors in the Kurdistan Region / Iraq - Barzan Omar Ali; Vian Sulaiman Hamasaeed; Ramyar Rzgar Ahmed (QALAAI ZANIST JOURNAL, 2022)
This study aims to demonstrate the importance of the effective role of audit committees in activating the governance of banks from the point of view of account auditors from the accounting perspective in Kurdistan Region of Iraq. In order to achieve the desired objectives of the research, the researchers prepared a questionnaire form and made use of some previous studies in the field of research. According to the five-point Likert scale (Strongly agree - agree - uncertain - disagree - Strongly disagree). One of the most important results that the research reached is that the audit committees are one of the main committees of the board of directors in the institution aimed at strengthening the credibility of the annual financial statements and reports, the quality of information for users, and the existence of a correlation and impact relationship for the effectiveness of audit committees in the effectiveness of banking governance. In light of these results, the researchers presented a set of recommendations, the most important of which is that it is necessary for banks to encourage audit committees to assume responsibility and give them the authority to choose the external auditor through material stimulation represented by rewards and intestinal stimulation represented by participation, creative thinking and brainstorming.